2018
DOI: 10.1016/j.ijmecsci.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Indentation in single-crystal 6H silicon carbide: Experimental investigations and finite element analysis

Abstract: Silicon carbide (SiC) is a promising material ideally suited for small-scaled devices deployed in harsh environments. SiC is brittle in bulk form, however, at small component length-scales plasticity is observed. A good understanding of deformation behaviour is, therefore, crucial for reliable small-scale component design and fabrication. Here, experimental and numerical analysis of the deformation behaviour of single-crystal 6H-SiC in nanoindentation is presented. Nanoindentation studies are carried out in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Most of these studies were aimed at understanding the global response of the material in which various mechanisms are active apart from defect evolution in single crystals such as grain boundary effects. Experimental nano-indentation studies have been used to measure the hardness of the material [17][18][19][20][21][22] and determine the elastic constant; but it should be noted that due to complex state of stress within the material (a combination of hydrostatic compression as well as that of shear depending upon the type of the indenter and distance of the indenter from the point being measured) in nano-indentation tests these cannot be effectively used for stress-strain determination and/or study of defect evolution within the material under a specific type of loading situation. Numerical studies of nanoindentation on the material has also been carried out [19,23] with an objective to explain the governing deformation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies were aimed at understanding the global response of the material in which various mechanisms are active apart from defect evolution in single crystals such as grain boundary effects. Experimental nano-indentation studies have been used to measure the hardness of the material [17][18][19][20][21][22] and determine the elastic constant; but it should be noted that due to complex state of stress within the material (a combination of hydrostatic compression as well as that of shear depending upon the type of the indenter and distance of the indenter from the point being measured) in nano-indentation tests these cannot be effectively used for stress-strain determination and/or study of defect evolution within the material under a specific type of loading situation. Numerical studies of nanoindentation on the material has also been carried out [19,23] with an objective to explain the governing deformation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental nano-indentation studies have been used to measure the hardness of the material [17][18][19][20][21][22] and determine the elastic constant; but it should be noted that due to complex state of stress within the material (a combination of hydrostatic compression as well as that of shear depending upon the type of the indenter and distance of the indenter from the point being measured) in nano-indentation tests these cannot be effectively used for stress-strain determination and/or study of defect evolution within the material under a specific type of loading situation. Numerical studies of nanoindentation on the material has also been carried out [19,23] with an objective to explain the governing deformation mechanisms. There exists other molecular dynamics (MD) simulation of 6H SiC (and/or other polytypes) under various types of complex loading conditions such as nano-cutting [24], nano scratching [23], sliding friction [25], ductile-regime machining [26][27][28] nuclear irradiation [29][30][31] and also shock studies [32][33][34]; however, almost all of these studies (including those in the referred literature of the above mentioned references) were primarily aimed at validating respective experimental results in a global sense rather than providing a detailed local mechanistic study into the cause of microstructural deformation induced in the sample under the applied loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Datye et al [23] evaluated the fracture toughness and plastic behavior of 6H-SiC single crystal by nanoindentation. Pang et al [24] conducted indentation experiments on 6H-SiC single crystal, and the results showed that classical crystal plasticity theory can be reliably applied in predicting the plastic deformation of ceramic at small scales. Goal et al [25] analyzed displacement controlled quasistatic nanoindentations on single crystal 4H-SiC, and an analytical stress analysis was carried out to calculate the theoretical shear strength and tensile stress.…”
Section: Introductionmentioning
confidence: 99%
“…Nawaz et al investigated the nanoscale elastic-plastic deformation behavior of single crystal 6H-SiC systematically by using nanoindentation with a Berkovich indenter and observed the effect of loading rates on the critical pop-in load, pop-in displacement and maximum shear stress [16]. Pang et al presented an experimental and numerical analysis of the deformation behavior of single-crystal 6H-SiC in nanoindentation, the results showed that classical crystal plasticity theory can be reliably applied in predicting plastic deformation of ceramic at small scales [17]. Lu et al described the mechanical planarization machining of SiC substrates involving the Si face and C face of N-type 4H-SiC, N-type 6H-SiC, and V-type 6H-SiC with a sol-gel polishing pad, the removal mechanism of SiC substrates was investigated by nanoindentation and nanoscratching [18].…”
Section: Introductionmentioning
confidence: 99%